Descompuneți în factori expresiile:
a) x²-2x-3
b)2x²-x-3
c)3x²+-1
d)-3x²-5x-2
Ajutațimă vărog
Răspunsuri la întrebare
Răspuns de
11
a) x²-2x-3=(x+1)(x-3)
x=-1, x=3
b)2x²-x-3=(x+1)(2x-3)
x=-1, x=3/2
c)3x²-1=-1/3(√3-3x)(3x+√3)
x=-1/√3, x=1/√3
d)-3x²-5x-2=-(3x+2)(x+1)
x=-2/3, x=-1
x=-1, x=3
b)2x²-x-3=(x+1)(2x-3)
x=-1, x=3/2
c)3x²-1=-1/3(√3-3x)(3x+√3)
x=-1/√3, x=1/√3
d)-3x²-5x-2=-(3x+2)(x+1)
x=-2/3, x=-1
Alte întrebări interesante
Matematică,
9 ani în urmă
Chimie,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă